Neurological and Musculoskeletal Features of COVID-19: A Systematic Review and Meta-Analysis - Abdullahi, Auwal; Candan, Sevim Acaroz; Abba, Muhammad Aliyu; Bello, Auwal Hassan; Alshehri, Mansour Abdullah; Afamefuna Victor, Egwuonwu; Umar, Naima Aliyu; Kundakci, Burak (Frontiers in Neurology, 2020)
Importance: Some of the symptoms of COVID-19 are fever, cough and respiratory difficulty. However, the mechanism of the disease including some of the symptoms such as the neurological and musculoskeletal symptoms is still poorly understood. Objective: The aim of this review is to summarize the evidence on the neurological and musculoskeletal symptoms of the disease. This may help with early diagnosis, prevention of the disease spread and plan of treatment. Data sources: MEDLINE, EMBASE, Web of Science and Google scholar (first 100 hits) were searched until April 17th, 2020. The key search terms used were “coronavirus” and “signs and symptoms.”Only studies written in English were included. Study selection: The selection was performed using EndNote and Rayyan softwares by two independent reviewers. Any disagreement was resolved by consensus meeting or by a third reviewer. Data extraction and synthesis: PRISMA guideline was used for abstracting data and assessing the quality of the studies. These were carried out by two and three independent reviewers respectively. Any disagreement was resolved by consensus meeting or by a third reviewer. The data was analyzed using qualitative synthesis and pooled using a random-effect model. Main Outcome(s) and Measure(s): The outcomes in the study include country, study design, participant details (sex, age, sample size); and neurological and musculoskeletal features. Result: Sixty studies (n=11, 069) were included in the review; and 51 studies were used in the meta-analysis. The median or mean age ranges from 24 to 95 years. The prevalence of neurological and musculoskeletal manifestations was 35% for smell impairment (95% CI 0-94%; I2 99.63%), 33% for taste impairment (95% CI 0-91%; I2 99. 58%), 19% for myalgia (95% CI 16-23; I2 95%), 12% for headache (95% CI 9-15; I2 93.12%), 10% for back pain (95% CI 1-23%; I2 80.20%), 10% for dizziness(95% CI 3-19%; I2 86.74%), 3% for acute cerebrovascular disease (95% CI 1-5%; I2 0%) and 2% for impaired consciousness (95% CI 1-2%; I2 0%). Conclusion and Relevance: Patients with COVID-19 present with neurological and musculoskeletal symptoms. Therefore, clinicians need to be vigilant in the diagnosis and treatment of these patients.